Critical Thinking of the Prophet Ibrahim Alaihissalam in the Qur'anic Perspective - Muzhoffar Akhwan (At-Tajdid: Jurnal Ilmu Tarbiyah, 2020)
The Alquran as a way of life for perfect humans. Humans should think critically in solving various life problems, because humans who are blind-minded will be blameworthy. Critical thinking based on the Alquran has 13 verses of Makkiyyah and 5 verses of Madaniyyah. In the Makkiyyah verse, Ibrahim is described as a prophet who warned his people and fathered two children, Ismail and Ishaq. In the Madaniyyah verse, Ibrahim is described as a Muslim who is upright in his stand, and an example for the people of Muhammad. Prophet Ibrahim As. as a great thinker not only experiences intellectual anxiety but also has a high concern for the fate of his people. Prophet Ibrahim As. made a lover of Allah (khalilullāh), because of his persistent consistency with monotheism. Critical thinking is a role model for learning for generations after. The results of this study found that critical thinking was the style of Prophet Ibrahim As. are: (1) The concept of critical thinking based on the Alquran in the form of istifhām inkāriy, which is a negative question, aims to arouse curiosity; (2) Critical Thinking in the style of Prophet Ibrahim As. to the universe and surrounding phenomena carefully about the oneness of Allah Rabbul 'Ālamīn as a convincing truth and (3) Implementation of critical thinking in the learning of Islamic Education (PAI) is carried out using an inclusive (open) paradigm, norm-oriented and religious ethics to solving social problems.